Teaching mathematics to adult students to promote higher education access - Belchior-Rocha, H.; Mauritti, R.; Monteiro, J.; Carneiro, L.; Mendes, J. (EDULEARN22 Proceedings, 2022)
The purpose of this paper is to present a model created at a public university with teaching mathematics to adult students who want to enter undergraduate degrees that require this area for entry. Attentive to the diversity of a group of students with very specific school and professional paths, distinct from those that correspond to the typical university student, new rules have recently been approved for evaluating the ability of students over 23 who do not hold a higher education entrance qualification. We are referring to students who have not gone on to further studies, students from vocational education, students from low-income families, or even students who will be the first in their families to attend higher education. Our unit is a support structure for the acquisition and development of essential skills, within the curricular structure of the courses of this university and has created a list of Preparatory Modules, namely: Topics of Elementary Mathematics I; Topics of Elementary Mathematics II; Geometry and Trigonometry; Logic, Succession, Combinatorial Calculus and Probabilities; Functions and Complex Numbers; Derivatives of Functions and Applications. Successful completion of the Mathematics Preparatory Course in the continuous assessment modality allows the student to use this classification for application purposes, without having to take the written test in mathematics. Our ministry of education, through decree-law 64/2006, of March 21, regulates the special conditions of access and entry to higher education for those over 23 years old without access qualification, regardless of academic qualifications. It is precisely to help create, reinforce and support this student coming from non-traditional paths that our preparatory courses serve. After 3 years of experience, the results are positive and the demand for these modules has increased substantially this program of capacitation allowed for the first time these students to have the possibility to enter a course in the areas of management and technology. The typical student who seeks this training offer has very diverse motivations: maybe self-motivated, or for reasons inherent to the professional culture, such as the need to update knowledge, may seek higher education also for certification, or avoid dismissal, at the employer's suggestion, or even because is obliged by the employer. ay also be exploring an area of personal interest that, for various reasons, has not been possible for you until now. Enrolling in a higher education course is a long-term commitment that can only be made by balancing employer, family, self-interest, and identity as a student, therefore it is necessary to create mechanisms to integrate this new public.